Osteosarcopenia in Patients with Chronic Obstructive Pulmonary Diseases: Which Pathophysiologic Implications for Rehabilitation? - Lippi, Lorenzo; Folli, Arianna; Curci, Claudio; D'Abrosca, Francesco; Moalli, Stefano; Mezian, Kamal; de Sire, Alessandro; Invernizzi, Marco (International journal of environmental research and public health, 2022)
Chronic obstructive pulmonary disease (COPD) is a burdensome condition affecting a growing number of people worldwide, frequently related to major comorbidities and functional impairment. In these patients, several factors might have a role in promoting both bone and muscle loss, including systemic inflammation, corticosteroid therapies, sedentary behaviours, deconditioning, malnutrition, smoking habits, and alcohol consumption. On the other hand, bone and muscle tissues share several linkages from functional, embryological, and biochemical points of view. Osteosarcopenia has been recently defined by the coexistence of osteoporosis and sarcopenia, but the precise mechanisms underpinning osteosarcopenia in patients with COPD are still unknown. In this scenario, a deeper understanding of the molecular basis of osteosarcopenia might guide clinicians in a personalized approach integrating skeletal muscle health with the pulmonary rehabilitation framework in COPD. Taken together, our results summarized the currently available evidence about the multilevel interactions between osteosarcopenia and COPD to pave the way for a comprehensive approach targeting the most common risk factors of these pathological conditions. Further studies are needed to clarify the role of modern clinical strategies and telemedicine solutions to optimize healthcare delivery in patients with COPD, including osteopenia, osteoporosis, and sarcopenia screening in these subjects.
Keywords: osteoporosis; lidé; chronic obstructive pulmonary disease; Pulmonary Disease, Chronic Obstructive; Osteoporosis; pulmonary rehabilitation; Risk Factors; chronická obstrukční plicní nemoc; rehabilitation; sarcopenia; Bone Diseases, Metabolic; dietary supplements; rizikové faktory; sarkopenie; metabolické nemoci kostí; osteoporóza; Sarcopenia; physical exercise; Humans